PERKEMBANGAN TAFSIR FALSAFI DALAM RANAH PEMIKIRAN ISLAM - Syafieh Syafieh (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
This article will explain about the development of philosophical interpretation from classical to modern era. The emergence of the medieval philosophical interpretation has provided a new insight into the development of interpretation. The existence of this style of philosophical interpretation is also the "gateway" of the advancement of thought in Islam. In the modern century came a new method of interpretation with a philosophical approach that is hermeneutic discourse. In the study, hermeneutical methods contain hermeneutical circles that should not be excluded one of them, namely text (text), author or author (outhor), and reader (reader) with text, context and contextualization. However, the discourse of hermeneutics has contributed greatly to the development of interpretive thought in the Islamic world. When hermeneutics is practiced in Islam. Hermeneutic interpretation not only understands the meaning of the Qur'anic text as God's word or context, but also on how the interpretation of the Qur'an as the spirit of the Muslim community to change its society for the better and the best.